Mechanism for Corrective Action on Budget Imbalances - Ion Lucian CATRINA (Transylvanian Review of Administrative Sciences, 2014)
The European Fiscal Compact sets the obligation for the signatory states to establish an automatic mechanism for taking corrective action on budget imbalances. Nevertheless, the European Treaty says nothing about the tools that should be used in order to reach the desired equilibrium of budgets, but only that it should aim at correcting deviations from the medium-term objective or the adjustment path, including their cumulated impact on government debt dynamics. This paper is aiming at showing that each member state has to build the correction mechanism according to the impact of the chosen tools on economic growth and on general government revenues. We will also emphasize that the correction mechanism should be built not only exacerbating the corrective action through spending/ tax based adjustments, but on a high quality package of economic policies as well.